Supply response in underdeveloped agriculture : A case study of four major annual crops in Thailand, 1937-1963 - Behrman, Jere R. (Amsterdam: North-Holland, 1968)
The book examines the policies for the expansion of agricultural production in underdeveloped countries especially in Thailand.
Includes index
Bibliography: p. 422-439.
usc 23/01/2019
Loans
Keywords: Agriculture--Economic aspects; Agriculture--Economic aspects--Mathematical models; Thailand